The Tarantula massive binary monitoring: V. R 144 a wind-eclipsing binary with a total mass ≳140 M[symbol sun] - Shenar, Tomer; Sana, H.; Marchant, P.; Pablo, B.; Richardson, N.; Moffat, A. F. J.; Reeth, T. Van; Barbá, R. H.; Bowman, D. M.; Broos, P.; Crowther, P. A.; Clark, J. S.; et al. (Astronomy and astrophysics, 2021)
Context. The evolution of the most massive stars and their upper-mass limit remain insufficiently constrained. Very massive stars are characterized by powerful winds and spectroscopically appear as hydrogen-rich Wolf-Rayet (WR) stars on the main sequence. R 144 is the visually brightest WR star in the Large Magellanic Cloud. R 144 was reported to be a binary, making it potentially the most massive binary observed yet. However, the orbit and properties of R 144 have yet to be established.Aims. Our aim is to derive the physical, atmospheric, and orbital parameters of R 144 and to interpret its evolutionary status.Methods. We performed a comprehensive spectral, photometric, orbital, and polarimetric analysis of R 144. We measured radial velocities via cross-correlation. Spectral disentangling was performed using the shift-and-add technique. We used the Potsdam Wolf-Rayet code for the spectral analysis. We further present X-ray and optical light curves of R 144, and we analyse the latter using a hybrid model combining wind eclipses and colliding winds to constrain the orbital inclination i.Results. R 144 is an eccentric (e = 0.51) 74.2−d binary comprising two relatively evolved (age ≈2 Myr), H-rich WR stars (surface mass fraction XH ≈ 0.4). The hotter primary (WN5/6h, T* = 50 kK) and the cooler secondary (WN6/7h, T* = 45 kK) have nearly equal masses of M sin3 i = 48.3 ± 1.8 M⊙ and 45.5 ± 1.9 M⊙, respectively. The combination of low rotation and H depletion observed in the system is reproduced well by contemporary evolution models that include boosted mass loss at the upper-mass end. The systemic velocity of R 144 and its relative isolation suggest that this binary was ejected as a runaway from the neighbouring R 136 cluster. The optical light curve shows a clear orbital modulation that can be explained as a combination of two processes: excess emission stemming from wind-wind collisions and double wind eclipses. Our light-curve model implies an orbital inclination of i = 60.4 ± 1.5°, resulting in accurately constrained dynamical masses of M1,dyn = 74 ± 4 M⊙ and M2,dyn = 69 ± 4 M⊙. Assuming that both binary components are core H-burning, these masses are difficult to reconcile with the derived luminosities (log L1,2∕L⊙ = 6.44, 6.39), which correspond to evolutionary masses of the order of M1, ev ≈ 110 M⊙ and M2, ev ≈ 100 M⊙. Taken at face value, our results imply that both stars have high classical Eddington factors of Γe = 0.78 ± 0.10. If the stars are on the main sequence, their derived radii (R* ≈ 25 R⊙) suggest that they are only slightly inflated, even at this high Eddington factor. Alternatively, the stars could be core He-burning, strongly inflated from the regular size of classical WR stars (≈ 1 R⊙); this scenario could help resolve the observed mass discrepancy.Conclusions. R144 is one of the few very massive extragalactic binaries ever weighed without the usage of evolution models, but poses several challenges in terms of the measured masses of its components. To advance, we strongly advocate for future polarimetric, photometric, and spectroscopic monitoring of R 144 and other very massive binaries.